The Relationship between Player’s Value Systems and Their In-Game Behavior in a Massively Multiplayer Online Role-Playing Game - Chaoguang Wang; Gino Yu (International Journal of Computer Games Technology)
This study examines the relationship between player’s value systems and their actions in playing a massively multiplayer online role-playing game. Online survey data from 1,577 players were paired with their behavioral metrics within the game. A number of correlations were found between the scores of value system and the in-game metrics. Participants that scored high on the Red value system tend to spend more real money in the game, level up their character and ability as quickly as possible, and seek other achievements in the forms offered by game world. These characteristics for fun, power, and immediate gratification are also predicted by the Red value system. The finding provides valuable information on how to better design, evaluate, and understand enjoyment in games. The results also show the possibility of using the game as a platform in inferring players’ value systems and in training people to develop certain skills.